1996
DOI: 10.1111/j.1469-8749.1996.tb15060.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine‐dependent Seizures: Demographic, Clinical, Mri and Psychometric Features, and Effect of Dose on Intelligence Quotient

Abstract: SUMMARY A regional population‐based survey identified six patients with pyridoxine dependency. Four presented on the first day of life and the other two at 1 and 8 months of age. Apart from multiple seizure types, other presenting features included jitteriness; encephalopathy, at first thought to be hypoxic‐ischaemic; hepatomegaly, and abdominal distension with bilious vomiting. Later problems included break‐through fits with fever; transient visual agnosia; squint; severe articulatory apraxia; motor delay wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 17 publications
5
97
4
Order By: Relevance
“…Not only is PDS characterised by seizures but also by encephalopathic symptoms such as agitation, jitteriness, irritability, startle reactions and feeding problems [16]. Reports on cerebral imaging have shown cerebral haemorrhage, non-specific white matter abnormalities, hydrocephalus, hypoplasia of the posterior part of the corpus callosum, cerebellar hypoplasia and a megacisterna magna [5,15,19,33]. At older age, cortical atrophy with ventricular dilation is sometimes observed in affected patients [5,15,34].…”
Section: Introductionmentioning
confidence: 99%
“…Not only is PDS characterised by seizures but also by encephalopathic symptoms such as agitation, jitteriness, irritability, startle reactions and feeding problems [16]. Reports on cerebral imaging have shown cerebral haemorrhage, non-specific white matter abnormalities, hydrocephalus, hypoplasia of the posterior part of the corpus callosum, cerebellar hypoplasia and a megacisterna magna [5,15,19,33]. At older age, cortical atrophy with ventricular dilation is sometimes observed in affected patients [5,15,34].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Interestingly, autistic behaviour and all these clinical features are also seen in children with pyridoxine-dependent epilepsy, whose seizures ceased with high doses of pyridoxine. [5][6][7] The observed similarity in these clinical features has led us to speculate that this subtype of PDDs might have a similar pathophysiological mechanism to pyridoxine-dependent epilepsy. Baxter and colleagues 6 reported that, after receiving high-dose pyridoxine, seizures ceased and intelligence quotient (IQ) scores improved among children with pyridoxine-dependent epilepsy.…”
Section: Andrew Roberts Dm Frcsmentioning
confidence: 99%
“…It has been reported that a long-term administration of pyridoxine may induce adverse effects such as a sensory peripheral neuropathy. 11 Third, we were unsure of the optimal dosage of pyridoxine to administer in this trial, but our use of 100 mg to 200 mg pyridoxine per day has been recommended by Baxter and colleagues 6,12 for the treatment of pyridoxine-dependent epilepsy. Fourth, we did not have an objective way to measure hypersensitivity to sound.…”
Section: Andrew Roberts Dm Frcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our adult subject demonstrates psychometric function slightly above previously averaged IQ values of children with PDS, in keeping with her early and continued therapy. It seems likely that preservation of intellect is dependent upon adequate pyridoxine replacement (Baxter et al 1996), but may vary with differing genotypes (Striano et al 2009;Scharer et al 2010) or unknown environmental influences (Alfadhel et al 2012). Further restoration of higher functions may prove possible with additional dietary modification such as lysine restriction (van Karnebeek et al 2012), emphasizing the complex pathogenesis of antiquitin defects beyond that of central pyridoxine deficiency.…”
Section: Treatment Prognosis and Risks Of Therapymentioning
confidence: 99%